The Project Work Pedagogy As A Means Of Constructing Knowledge For Learners Of The Secondary Level In Algerian Schools - Habitouche, Mustapha; Abdellatif ,Naouel (My University, 2025)
Abstract: This research attempts to clarify practical issues regarding the competency-based system by providing a tangible example of the project-based learning approach, which was initially implemented in English teaching and learning at the secondary level beginning in 2004. The study demonstrates how students can build their own knowledge by utilizing the project work approach that was included in the recently implemented CBC curriculum. It goes on to explain the usage of project work in the context of the English as a Foreign Language curriculum and how teachers might offer it to students as a technique of building knowledge.
Keywords: Project work; Competency-based Approach; Constructivism; Cognitivism; Problem Solving